The making of Southeast Asian nations : state, ethnicity, indigenism and citizenship - Suryadinata, Leo (Singapore : World Scientific, 2015)
'The book aims to examine the making of the nations in Southeast Asia using both historical and political science approaches. Concepts related to nations such as ethnicity, state, indigenism and citizenship have also been analysed in the Southeast Asian context. Specific examples of nation-building in five major Southeast Asian countries are presented. Problems and prospects of Southeast Asia's nation-building and citizenship building in the era of globalisation are also discussed'--
Multiethnic society, conflict regulation and nation-building -- Nation, state, ethnicity and indigenism -- Nation, citizenship and indigenism -- Ethnicity, indigenism and Southeast Asia's citizenship laws -- Ethnic Chinese and the formation of Southeast Asian nations -- China's citizenship laws and Southeast Asian Chinese -- Nation-building or citizenship-building in Singapore? -- Indigenism, Islam and nation-building in Malaysia -- Ethnicity, Islam and nation-building in Indonesia -- The Philippines and Thailand: ethnicity and Islam in nation-building -- Citizenship, nation-state, and nation-building in the globalizing Southeast Asia.
Includes bibliographical references (pages 309-320) and index.
Keywords: Civil society -- Southeast Asia; Nation-state and globalization -- Southeast Asia; Citizenship -- Southeast Asia; Islam and state -- Southeast Asia; Chinese diaspora; Ethnicity -- Political aspects -- Southeast Asia